Revival of the Abbasid caliphate in Cairo In light of inscriptions on Mamluk coins 659) AH/ 1261CE) - Barakat, Elshahat Anwar (Arab Journal for Sciences and Research Publishing, 2020)
The study aimed to address the revival of the Abbasid Caliphate in Cairo, after it fell at the hands of the Mughal advance in the fall of Baghdad in 656 AH, so the Abbasid Caliphate fell and the Mongols took control of its capital, Baghdad, and killed the last Abbasid caliphs, the Sultan Al-Mustasim slaughtered in 656 AH, and since then Muslims did not have a state that defends them and fights under its flag except the Mamluk state in Egypt, which responded to the Mongol attacks on the Islamic world, and the Mamluks managed to defeat the Mongols in the famous battle of Ain Jalut 658 AH, which was the beginning of the true breakdown of the Mongol advance to the Islamic world, and the Mamluk victories continued over the Mongols. After that, many of the Islamic countries they had conquered were liberated at the beginning of their encroachment on Muslim countries.The Mamluks were then the campaigners of the jihad brigade and raised their banner against the Mongols, and they also became the actual rulers of Egypt and the Levant since then with the right of the sword and the power they possessed, especially after they rid the Islamic world of the attacks of the Mongols who terrorized people and killed hundreds of thousands and could only stand in the face of them. Mamluks, so people condemned the Maliki and satisfied their rule.However, the Mamluks themselves saw a lack of their rule as if the specter of slavery in which they lived before they became rulers continued to haunt them, and the matter increased during the reign of Zahir Baybars, who tried to legitimize his rule and the rule of the Mamluks after him, so he took many measures to achieve that and the most important of these The measures are "reviving the Abbasid caliphate in Cairo," which had fallen in its capital, Baghdad, after the Mongol attacks and the fall of Baghdad in their hands, so that the city of Cairo became the incubator of the caliphate and its new patron during the Mamluk era, but this time the caliphate did not become an absolute authority as it was before, but rather Imaginary power behind which the Mamluks rule the Islamic countries, so the position of the caliphate was divided into two parts of the religion of the Abbasid caliph and the politician of the apparent Baybars, and the title of the apparent Baybars Qasim, the Commander of the Faithful, a metaphor for the sharing of the position of the caliphate between him and the Abbasid caliph, and struck that on the money that was silenced in his era, which is more accurate Witness the new changes in the conditions of the Abbasid Caliphate, as well as the Mamluk Sultanate in Egypt.And this research that is in our hands will address this topic through a descriptive study of the writings and inscriptions on Mamluk money minted in Egypt during that period.The researcher found that:1- the Abbasid Caliphate was merely a mere caliphate that had no strength in that period.2- the researcher recommended the necessity of studying archeology and archaeological writings from a historical point of view as a primary source for documentation and validation of historical information.
Keywords: Abbasid Caliphate; Mamluk State; Inscriptions; Coins